Restorative justice and practice in US education - Roth, Kenneth R.; Kumah-Abiwu, Felix; Ritter, Zachary S. (Palgrave Macmillan, 2024)
Chapter 1. Restorative Practice: Background and framework -- Chapter 2. Maximizing Restorative Justice: Altering Structural Injustices First -- Chapter 3. Humanizing Classrooms within De-Humanizing Systems: Restorative Justice Education in Teacher Education -- Chapter 4. Restorative Practice as a pathway for healing from Indian Boarding schools and Indian Residential schools -- Chapter 5. Emotional Labor, Emotional Work, and the Question of “Help” in Harm -- Chapter 6. Cancel culture and the impact on restorative approaches in BIPOC communities -- Chapter 7. Now What? -- Chapter 8. Practical and Purposeful Restorative practice in K-12 -- Chapter 9. Supporting children to navigate crisis repair: A conversation of everyday bullying and how schools fail us -- Chapter 10. Restorative Practice in healthcare: Case studies from academic medicine -- Chapter 11. Restorative Justice in Higher Education: A Review of the Literature -- Chapter 12. Our Restorative Justice Mistake: A Collaborative Approach to Reintroducing and Decentralizing Restorative Practice in Higher Education -- Chapter 13. Sustained restorative dialogue to understand and address structural sources of harm in university communities -- Chapter 14. Doctoral education as “doing with”: A restorative approach to qualitative research training -- Chapter 15. Restorative Supervision in Student Affairs/Higher Education.